2011
DOI: 10.1007/s11999-011-1848-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Total Ankle Arthroplasty A Cost-effective Alternative to Ankle Fusion?

Abstract: Background Total ankle arthroplasty (TAA) implantation is increasing, as the potential for pain relief and restoration of function and risks are compared with those for ankle fusion. A previous analysis with a simple decision tree suggested TAA was cost-effective compared with ankle fusion. However, reevaluation is warranted with the availability of newer, more costly implants and longer-term patient followup data. Questions/purposes Considering all direct medical costs regardless of the payer, we determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 16 publications
1
73
1
3
Order By: Relevance
“…Courville et al used a Markov model and concludes that TAR is a cost-effective alternative to ankle fusion [21]. 1 OA 75 135 27 2 23 14 5 2 Pta 65 51 31 1 127 31 2 3 RA 63 134 20 4 31 19 3 4 HChr 64 50 36 2 65 35 1 5 Pta 63 141 30 1 85 26 2 6 OA 57 68...…”
Section: Discussionmentioning
confidence: 99%
“…Courville et al used a Markov model and concludes that TAR is a cost-effective alternative to ankle fusion [21]. 1 OA 75 135 27 2 23 14 5 2 Pta 65 51 31 1 127 31 2 3 RA 63 134 20 4 31 19 3 4 HChr 64 50 36 2 65 35 1 5 Pta 63 141 30 1 85 26 2 6 OA 57 68...…”
Section: Discussionmentioning
confidence: 99%
“…Bonnin et al noted 65.2% after 10 years in TAR using the Salto Prosthesis (14). Furthermore, Courville et al concluded in a costeffective analysis of a hypothetical 60 year old cohort that TAR remained cost effective alternative to ankle arthrodesis despite newer costly implants and longer follow-up (15).…”
Section: Ankle Arthroplastymentioning
confidence: 99%
“…Another retrospective study examined the effect of complications after both procedures and found comparable outcomes in terms of pain relief and improved function compared with the preoperative baseline; however, the study again showed a significantly greater rate of complications in the arthroplasty group (86). The economics of arthroplasty versus arthrodesis have also been examined, and arthroplasty has been found to be cost-effective despite more expensive implants and a longer follow-up period (87).…”
Section: Comparison Of Total Ankle Arthroplasty Versus Ankle Arthrodesismentioning
confidence: 99%